Keterampilan Membaca Pemahaman Siswa Kelas VII SMP Negeri 17 Sarolangun dalam Pembelajaran Teks Prosedur - Wirdanengsih; Syahrul Ramadhan (Lembaga Yasin AlSys, 2026)
Although reading comprehension skills have received considerable attention in studies on Indonesian language learning, research specifically examining their role in procedural text learning among seventh-grade students remains limited. This study aimed to describe the reading comprehension skills of seventh-grade students at SMP Negeri 17 Sarolangun and analyze their relationship with procedural text learning. The study employed a quantitative approach with a correlational design and involved 61 students selected through proportionate stratified random sampling from a population of 154 students. Data were collected using an objective reading comprehension test and analyzed through a normality test, simple correlation, simple linear regression, a significance test, and the coefficient of determination. The results showed that the reading comprehension data were normally distributed, with a significance value of .058. The correlation analysis yielded a coefficient of .472 with a significance value of p < .001, while the simple linear regression analysis showed that reading comprehension skills contributed 22.3% to procedural text learning. These findings demonstrate the importance of reading comprehension skills in helping students identify the content, structure, sequence of steps, and instructional meaning of procedural texts. This study concludes that reading comprehension skills play a role in procedural text learning. These findings imply that teachers should systematically implement guided reading, text structure analysis, and exercises in understanding procedural information to strengthen students’ ability to comprehend procedural texts.